1995
DOI: 10.1557/jmr.1995.0312
|View full text |Cite
|
Sign up to set email alerts
|

Microwave characteristics of BaPr2Ti4O12 and BaPr2Ti5O14 ceramics

Abstract: 5 Oi4 ceramics which have extremely similar crystal structures, were investigated, including those of the solid solution represented by the formula of Ba 6 _ ;c Pr 8+ 2^3Ti 18 054 ceramics. It is suggested that BaP^TisO^ ceramics are composed of mixed phases, approximately 85.0 vol. % Ba4.o5Pr9. 3 Tii 8 0 5 4 (x = 1.95), 8.1 vol. % TiO 2 , and 6.9 vol. % BaTi 4 O 9 . The microwave dielectric properties of the Ba 6 _ x Pr 8+ 2 X / 3 Ti 18 O 5 4 system are strongly dependent on the x value, which is interesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Negas et al [28] observed similar variations for Smand Nd-based ceramics. Fukuda et al [76] found a similar enhancement of Qf at x = 2/3 in Ba 6-3x Pr 8 þ 2x Ti 18 O 54 . At x = 2/3, Ln and Ba ions occupy separately the rhombic sites (A1) and the pentagonal sites (A2) respectively and at this composition the ceramics showed a maxima in Qf.…”
Section: Dielectric Propertiesmentioning
confidence: 72%
See 1 more Smart Citation
“…Negas et al [28] observed similar variations for Smand Nd-based ceramics. Fukuda et al [76] found a similar enhancement of Qf at x = 2/3 in Ba 6-3x Pr 8 þ 2x Ti 18 O 54 . At x = 2/3, Ln and Ba ions occupy separately the rhombic sites (A1) and the pentagonal sites (A2) respectively and at this composition the ceramics showed a maxima in Qf.…”
Section: Dielectric Propertiesmentioning
confidence: 72%
“…Several authors studied [3,5,10,11,13,16,19,21,29,41,57,56,[66][67][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] the dielectric properties of Ba 6-3x Ln 8 þ 2x Ti 18 O 54 ceramics for different values of x and Ln = La, Pr, Sm, Nd, Eu, Gd and are given in Table 5.3. A study of Table 5.3 shows that the ceramics based on Eu, Sm and Nd have high quality factors (Qf) up to 14 000 GHz.…”
Section: Dielectric Propertiesmentioning
confidence: 99%
“…TTB thin film exhibits a permittivity ε r = 135 at 10 GHz, 130 at 20 GHz, and 125 at 30 GHz showing a good stability versus frequency (Figure 11a). Even though the literature does not present many microwave dielectric characterizations of the TTB phases, permittivity values close to 130 have also been reported for other materials [45,46]. Nevertheless, these values remain lower than those retrieved from the K x Na 1-x NbO 3 perovskite phase in the same settings [47].…”
Section: High Frequency Measurementsmentioning
confidence: 76%
“…Clearly, the trend is violated by Gd which, although smaller than Eu, exhibits a very low Q• f value of 2050 GHz. [3][4][5][6][7] The samples for the dielectric property measurements were prepared from reagent-grade BaCO 3 , Sm 2 O 3 , and TiO 2 . The starting reagents were mixed in the appropriate ratios and homogenized by ball milling.…”
mentioning
confidence: 99%